CERAMICS OF IRGANAI SETTLEMENT I ACCORDING TO THE RESULTS OF RESEARCH IN 2006 - Sajpudinov, M S (History, Archeology and Ethnography of the Caucasus, 2017)
The article deals with the ceramics of Irganai settlement I of the Middle and early stage of the Late Bronze Age, revealed during excavations in the area of construction of Irganai hydroelectric station.The analysis of the ceramic complexes of the settlement is based on the results of the expedition of 2006. Taking into consideration the papers on the study and typological characteristics of ceramics, the author analyzes the size of the ceramic complexes, describes the ornaments, conducts comparative analysis of the ceramic materials and presents classification of the forms and types of the vessels. Besides, the author of the article introduces into scientific use the ceramic materials obtained during the excavations of the Irganai settlement I in 2006. Only fragments of clay vessels are considered in the article. Whole vessels were not found. In total, 667 fragments of clay vessels were found during the clearing of cultural layer P-II in 2006, and basing on them, the author presents typological characteristics of the ceramics resulting from comprehensive analysis. The identified types of vessels of Irganai settlement I have close analogies in the sites of early stage of the Middle Bronze Age of Mountainous Dagestan and Southeast Chechnya. There are some parallels in the ceramics of contemporaneous sites of submontane(Chirkey, Miatli) and maritime (Manas) Dagestan. The general nature of ceramics, similarity of clay body and fragment structure, which have analogies in the ceramics of Irganai burial I and Irganai settlement II, allow to suggestthat these sites are contemporaneous and belong to the Ginchi-Gatynkali culture of early stage of the Bronze Age.